Diverting Hydrogenations with Wilkinson's Catalyst towards Highly Reactive Rhodium(I) Species. (6th October 2015) - Perea‐Buceta, Jesus E.; Fernández, Israel; Heikkinen, Sami; Axenov, Kirill; King, Alistair W. T.; Niemi, Teemu; Nieger, Martin; Leskelä, Markku; Repo, Timo
Abstract: The addition of Barton's base has a dramatic effect on the classic rhodium(III)‐mediated hydrogenations promoted by Wilkinson′s catalyst. Following the initial oxidative addition, a barrierless reductive elimination of HCl from the traditional rhodium(III) intermediates instantly produces a rhodium(I) monohydride species, which is remarkably reactive in the hydrogenation of several internal alkynes and functionalized trisubstituted alkenes. The direct formation of this species is unprecedented upon addition of molecular hydrogen and its catalytic potential has been hitherto barely explored.